The Uniqueness of Clear Cell Renal Cell Carcinoma: Summary of the Process and Abnormality of Glucose Metabolism and Lipid Metabolism in ccRCC - Qi, Xiaochen; Li, Quanlin; Che, Xiangyu; Wang, Qifei; Wu, Guangzhen (Frontiers in Oncology, 2021)
Kidney cancer is one of the cancers with increasing incidence in recent years. ccRCC accounts for a very high proportion of kidney cancers, up to 80%. The understanding of the pathogenesis, tumor progression, and metastasis of renal carcinoma is not perfect. At present, the mainstream view on renal cancer is based on abnormal metabolic diseases, mainly with abnormal fatty acid and cholesterol metabolism, while related abnormal glucose metabolism, including the conversion between lactic acid and pyruvate, will have an impact on cancer. We start from the representative phenomenon of abnormal cancer metabolism: Warburg effect, through the collection of popular metabolic pathways and related genes in the last decade, as well as some research hotspots including the role of ferroptosis and glutamine in cancer, systematically elaborated the factors affecting the incidence and metastasis of kidney cancer. The most significant pathological feature of ccRCC cells is the accumulation of lipid droplets. We described in detail the formation process of renal carcinoma, especially the pathological morphology of ccRCC, to explore the relationship between it and abnormal lipid metabolism, and to find out the role of related genes in renal carcinoma, whether they are protective genes or risk genes. This review finds the similarities and differences between kidney cancer and other cancers in order to lay a theoretical foundation and provide a valid hypothesis for future research.